Experimental Investigation on Effect of Kusum and Safflower Oil Methyl Ester in a VCR Engine - Kumar, Nitin (My University, 2017)
Due to continuous increase in the dependency on fossil fuels and hiking its price because of fast depletion of petroleum resource have promoted to the shift toward green energy sources such as alternative renewable and sustainable fuel. Biodiesel has been recognized as clean and potential renewable fuel which is obtained from biomass resources and animal fats. The aim of this experimental investigation is to optimize biodiesel production from safflower and kusum seed oil followed by transesterification process. As per consideration of maximum biodiesel yield, the optimum parameters were 4:1 molar ratio, 1.5% KOH catalyst concentration, 75 minutes reaction time and 6:1 molar ratio, 1% KOH catalyst concentration, 60 minutes reaction time followed by safflower and kusum oil methyl ester production respectively. The yield of safflower and kusum oil methyl ester corresponding to optimized process parameters were 97.07% and 90.34% respectively. Three types of blended fuels B10, B20 and B30 of each biodiesel have been studied and all tests were carried out in variable compression ratio (VCR) engine at constant speed 1500 rpm, compression ratio 17:1 under different load conditions. The various performance, emission and combustion characteristics like brake power (BP), brake thermal efficiency (BThE), brake specific fuel consumption (BSFC), mechanical efficiency (MEff), carbon monoxide (CO), hydrocarbon (HC), nitrogen oxide (NOx), exhaust gas temperature (EGT), peak cylinder pressure and heat release rate (HRR) were evaluated. It was observed that the performance of all blended fuels of safflower oil biodiesel almost same to the diesel fuel and B20 blend fuel of kusum oil biodiesel showed better performance among the all tested fuels KB10, KB30 and standard diesel. The emissions of CO, HC decreased by increasing percentage proportion of biodiesel in blend fuel and apart from that NOx, EGT were increased. It was concluded that by comparing the SOME and KOME blend fuels, the overall performance of KOME blend fuels have been noticed better than that of SOME blend fuels.
ME-Thermal Engineering
Keywords: Biodiesel; Transesterification; Performance; Emission